Gut Microbiota and Brain Aging: Identifying Keystone Biomarkers for Cognitive Health - Muskan Bhatia; Sidharth P. Mishra; Raghvendra K. Mishra; Shalini Jain; Hariom Yadav; Rajesh S. Tomar (Biomedicines, 2026)
The fact that the population is getting older has greatly increased the occurrence of cognitive decline and neurodegenerative diseases, underlining the importance of having reliable biomarkers that can measure biological aging before irreversible neurological damage takes place. New evidence shows that brain aging is not just the result of changes within neurons themselves but is also greatly affected by the gut microbiota via immune, metabolic, endocrine, and neurovascular signaling. This review brings together the existing knowledge about biomarkers of biological aging-such as telomere shortening, epigenetic clocks, oxidative stress, inflammation, cellular senescence, and metabolic dysfunction-as well as established cognitive biomarkers obtained from neuroimaging, cerebrospinal fluid, blood, genetic evaluations, and neuropsychological tests. We also point out that changes associated with age in the composition of the gut microbiota and the metabolites it produces are becoming more and more involved in the mechanisms connecting intestinal dysbiosis, dysfunction of the blood-brain barrier (BBB), neuroinflammation, and age-related cognitive decline. Through this approach of combined and complementary biomarker systems, we hypothesize that the gut microbiota has emerged as a central regulator of biological and cognitive aging and may provide a useful source for development of biomarkers of cognitive resilience and risk of neurodegenerative diseases. Lastly, we consider microbiome-based interventions, including probiotics, prebiotics, dietary changes, fecal microbial transplant, and new treatment modalities derived from molecular studies, as possible approaches to the prevention and management of age-related cognitive decline. Collectively, this review provides a comprehensive framework linking aging biology, microbiome science, and cognitive biomarkers to advance biomarker-driven precision medicine for healthy brain aging.